EDUKASI MENGENAI POLA HIDUP BERSIH DAN SEHAT DI SDN 18 BUKIT KECIL KABUPATEN PESISIR SELATAN - Saputra, Muhammad Rizki; Tosi Rahmaddian; Irwadi, Irwadi; Rahma Triyana; Rifkind Malik; Nana Liana; Ruhsyahadati, Ruhsyahadati; Suharni, Suharni; Roland Helmizar; Sri Wahyuni; Alief Dhuha; Betty Fitriyasti1 (Nusantara Hasana Journal, 2025)
Clean and Healthy Living Behavior (PHBS) refers to a conscious effort by individuals to adopt healthy habits in their personal lives, within their families, and in the broader community. PHBS aims to prevent health problems through simple yet effective daily practices. The role of parents, the environment, and teachers is crucial in shaping students' behavior, especially during childhood. However, many elementary school students still lack sufficient knowledge about the importance of clean and healthy living habits. Therefore, educational initiatives are necessary to instill these positive behaviors from an early age. The session was carried out in an educational and interactive manner, incorporating direct practice, games, and quizzes. The PHBS education program took place at SDN 18 Bukit Kecil, Pesisir Selatan Regency, involving 30 student participants. The activity had a clear positive impact on students' knowledge and behavior regarding clean and healthy living practices. The success of the program was supported by strong collaboration between the community service team and the school. It is hoped that similar initiatives will continue to be implemented on a regular basis to cultivate a culture of clean and healthy living from an early age.